Spectral theory, mathematical system theory, evolution equations, differential and difference equations : 21st International workshop on operator theory and applications, Berlin, July 2010 - Arendt, Wolfgang (Operator Theory: Advances and Applications, 2012)
The present volume contains a collection of original research articles and expository contributions on recent developments in operator theory and its multifaceted applications. They cover a wide range of themes from the IWOTA 2010 conference held at the TU Berlin, Germany, including spectral theory, function spaces, mathematical system theory, evolution equations and semigroups, and differential and difference operators. The book encompasses new trends and various modern topics in operator theory, and serves as a useful source of information to mathematicians, scientists and engineers.